Experimental evidence of lower hybrid wave scattering in Alcator C-Mod due to scrape off layer density fluctuations. (23rd May 2019) - Martin, E.H.; Lau, C.; Wallace, G.M.; Shiraiwa, S.; Mumgaard, R.T.
Abstract: Novel experimental measurements of the lower hybrid (LH) wave electric field vector, E LH, obtained in Alcator C-Mod using dynamic Stark spectroscopy are presented. Three key results were obtained by comparison with 3D full-wave COMSOL simulations using the cold plasma dielectric tensor and reflectometry-measured density profiles. (1) As a function of space and LH power, the magnitude ofE LH was found to agree with the full-wave simulation result. (2) The direction ofE LH was found to have a substantial poloidal component and is in strong disagreement with the nearly radial full-wave simulation result. (3) The addition of scrape off layer density fluctuations to the density profile implemented in the full-wave simulations can be used to explain theE LH direction discrepancy. It is concluded that diffraction and scattering by turbulence-driven scrape off layer density fluctuations is the responsible mechanism behind the modification in the direction ofE LH . These results further support the previously reported proposition that edge turbulence is an important mechanism behind the strong anomalous drop in LH current drive efficiency for diverted plasmas in the high-density regime.